Multi-environment evaluation of rice genotypes: impact of weather and culm biochemical parameters against sheath blight infection - Panda, Siddharth; R., Naveen kumar; Pavani S., Lalitha; Ganesan, Sangeetha; Singh, Pawan Kumar; Sah, Rameswar Prasad; V., Padmakumar; Subudhi, Hatanath; Mahender, Anumalla; Anandan, Annamalai; Ali, Jauhar (Frontiers in Plant Science, 2023)
Multi-environment evaluation of 32 rice genotypes against sheath blight infection was conducted over six seasons across two locations (Agricultural Research Farm, Institute of Agricultural Sciences, Banaras Hindu University (28.18o N, 38.03o E, and 75.5 masl), for four years during the wet season (Kharif) from 2015 to 2018 and two seasons at National Rice Research Instuite (20o27’09” N, 85o55’57” E, 26 masl), Cuttack, Odisha, during the dry season (rabi) of 2019 and kharif of 2019), including susceptible and resistant checks. Percent disease index data were collected over four weeks (on the 7th day, 14th day, 21st day, and 28th day after infection), along with data on other morphological and physiological traits. The resistant genotypes across seasons were the ones with higher hemicellulose content (13.93-14.64) and lower nitrogen content (1.10-1.31) as compared with susceptible check Tapaswini (G32) (hemicellulose 12.96, nitrogen 1.38), which might explain the resistant reaction. Three different stability models – additive main effect and multiplicative interaction (AMMI), genotype + genotype x environment (GGE) biplot, and multi-trait stability index (MTSI) – were then used to identify the stable resistant genotypes across six seasons. The results obtained with all three models had the common genotypes highlighted as stable and having low area under the disease progress curve (AUDPC) values. The ideal stable genotypes with low disease incidence were IC 283139 (G19), Tetep (G28), IC 260917 (G4), and IC 277274 (G10), with AUDPC values of 658.91, 607.46, 479.69, and 547.94, respectively. Weather parameters such as temperature, rainfall, sunshine hours, and relative humidity were also noted daily. Relative humidity was positively correlated with the percent disease index (PDI) mean, whereas temperature had a negative correlation. Rabi 2019 and 2016 displayed the highest PDI mean of all seasons, attributed to low active sunshine hours and favorable relative humidity.